2008
DOI: 10.1002/ajmg.a.32322
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between public attitudes toward genomic studies related to medicine and their level of genomic literacy in Japan

Abstract: The aim of this study was to assess public attitudes toward the promotion of genomic studies related to medicine and to examine the relationship between public attitudes and the level of genomic literacy by analyzing data from a nationwide opinion survey. The participants comprised 4,000 people (age, 20-69) selected from the Japanese general population by using the two-step stratified random sampling method. They were queried on the following topics in a mail survey: (1) pros and cons of the promotion of genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
75
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(81 citation statements)
references
References 16 publications
4
75
2
Order By: Relevance
“…Following these analyses, multivariable models were built for the significantly associated variables controlling for potential confounding variables. Based on the findings of previous studies [19,29,31], sociodemographic factors considered as potential confounders in health literacy and genetic knowledge models included gender, race, levels of education, language of survey administration, and place of birth. Multiple linear regression models were fitted for the continuous outcomes (genetic knowledge, health literacy) using gender, race, educational attainment, survey language, and place of birth as covariates; regression coefficients and respective p values are reported.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Following these analyses, multivariable models were built for the significantly associated variables controlling for potential confounding variables. Based on the findings of previous studies [19,29,31], sociodemographic factors considered as potential confounders in health literacy and genetic knowledge models included gender, race, levels of education, language of survey administration, and place of birth. Multiple linear regression models were fitted for the continuous outcomes (genetic knowledge, health literacy) using gender, race, educational attainment, survey language, and place of birth as covariates; regression coefficients and respective p values are reported.…”
Section: Methodsmentioning
confidence: 99%
“…about heredity, genetic tests, genetic determinism) among Dutch [29] and Finn [30] adults as well as higher genetic literacy (i.e. genetic terminology, contextual understanding) among younger Japanese than older [31]. To our knowledge, studies evaluating differences by age in general knowledge about genetics and heredity among a population at average disease risk have not been conducted in the U.S. in recent years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focus groups have described a lack of awareness regarding personalized medicine, and concerns regarding its use, but also a willingness from the participants to learn more about it [16,17,18,19,20]. Surveys from outside the US show public support for personalized medicine, albeit with concerns regarding cost, privacy and patient sovereignty [21,22,23,24,25]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported positive public attitudes about genetic research and genetic testing. [1][2][3][4] Although some studies have reported low levels of public understanding of genetic concepts, 3,5,6 the general knowledge level may be increasing. 6 In comparison, little data are available about researchers' views of public understanding and interest in science, particularly genetics and genomic research.…”
Section: Introductionmentioning
confidence: 99%